Interleukin-15 and chemokine ligand 19 enhance cytotoxic effects of chimeric antigen receptor T cells using zebrafish xenograft model of gastric cancer - Zhou, Zhifeng; Li, Jieyu; Hong, Jingwen; Chen, Shuping; Chen, Mingshui; Wang, Ling; Lin, Wansong; Ye, Yunbin (Frontiers in Immunology, 2022)
Chimeric antigen receptor (CAR) T cells have been proven effective for the treatment of B-cell-mediated malignancies. Currently, the development of efficient tools that supply CAR T cells for the treatment of other malignancies would have great impact. In this study, interleukin (IL)-15 and C-C motif chemokine ligand 19 (CCL19) were introduced into natural killer group 2D (NKG2D)-based CARs to generate 15×19 CAR T cells, which remarkably increased T-cell expansion and promoted the production of central memory T (Tcm) cells. 15×19 CAR T cells showed greater cytotoxicity to gastric cell lines than conventional CAR T cells and produced higher levels of IL-15 and CCL-19, which resulted in increased responder T cell chemotaxis and reduced expression of T cell exhaustion markers. A live zebrafish model was used for single-cell visualization of local cytotoxicity and metastatic cancers. Administration of 15×19 CAR T cells resulted in significant shrinking of gastric cancer xenograft tumors and expansion of 15×19 CAR T cells in zebrafish models. Taken together, these findings demonstrate that 15×19 CAR T cells are highly efficient in killing gastric cancer cells, are effective to avoid off-target effects, and migrate to local and metastatic sites for long-term surveillance of cancers.